STRATEGI PENGEMBANGAN KEPARIWISATAAN DI KOTA BUKITTINGGI - Sanesta, Aldian; Rusli SD, Zaili (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Development Strategy of turism at Bukittinggi City. Bukittinggi City Tourism Development is an area of the city and one of the main tourist destination in West Sumatra with the introduction of Bukittinggi as a "City Tour" starting since March 11, 1984. Field of tourism in the regions designated as potential Bukittinggi based on natural and geographical conditions of Bukittinggi, its strategic position is a triangle crossing to the north, east and south of Sumatra that eases access tourists or people who want to visit a small city with myriads of this story. Besides having the natural beauty of the city of Bukittinggi is also a struggle that many stores the value of history and cultures in it.Under these conditions, formulated the problem of how the development of tourism in the city of Bukittinggi and the factors that influence the development of tourism in the city of Bukittinggi. This study uses the theory Elittan to determine strategies used in the development of tourism in the city of Bukittinggi, qualitative research with descriptive method. Researchers are trying to reveal the facts in accordance with the reality. This study did not look for or explain ties, not test hypotheses or make predictions. Data will be explained with apaa danya to obtain an understanding. From the results of this study concluded that the strategy of development of tourism in the city of Bukittinggi to involve the whole among the noble of the Stakeholde, community stempat and the nomads with the concept of Tourism-based community that creates a sense of tourism awareness and stepping to the strategy undertaken in the development of tourism can run well , but still a bit constrained in the implementation on the ground in the form of regional financial, qualified human resources, limited investment in tourism, the lack of development of tourism products as well as coordination across sectors that have not been together but slowly but surely constraints faced in the development of tourism in the city of Bukittinggi will be minimized so that tourism in the town Bukttinggi can provide maximum service and bestKey word : Strategy ,Turism Development, Tour City